Neural Correlates of the Poggendorff Illusion Driven by Illusory Contour: An fMRI Study - Qi Chen; Li Li (i-Perception, 2011)
The Poggendorff illusion is a well-documented geometric illusion that involves the brain's perception of the interaction between oblique lines and object contours: an oblique line is apparently misaligned once interrupted by two parallel contours. This illusion occurs even when the parallel contours are defined subjectively or illusorily. In this fMRI study, we adopted a 4 (type of stimuli: Poggendorff illusion under real contour and its corresponding control condition; Poggendorff illusion under illusory contour and its corresponding control condition) by 4 (degree of angle between the oblique line and the two vertical contours: 22.5°, 45°, 67.5°, and 90°) factorial design to investigate the neural correlates of Poggendorff illusion induced by real and illusory contours. By computing the parametric modulation effect of the angle for different type of stimuli, we found that, as compared with the control conditions, the two types of Poggendorff illusion conjointly activated the right intraparietal sulcus (IPS). Moreover, the right IPS was involved in the neural interaction between the two types of illusions by showing higher neural activity in the illusory than in the real contour condition. Taken together, our results suggest that the right IPS is responsible for constructing the Poggendorff illusion driven by illusory contours.